2022
DOI: 10.1111/age.13248
|View full text |Cite
|
Sign up to set email alerts
|

Non‐contact detection method of pregnant sows backfat thickness based on two‐dimensional images

Abstract: Since sow backfat thickness (BFT) is highly correlated with its service life and reproductive effectiveness, dynamic monitoring of BFT is a critical component of large‐scale sow farm productivity. Existing contact measures of sow BFT have their problems including, high measurement intensity and sows' stress reaction, low biological safety, and difficulty in meeting the requirements for multiple measurements. This article presents a two‐dimensional (2D) image‐based approach for determining the BFT of pregnant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…In order to solve the problems of time consumption, relative inefficiency, equipment constraints, and the influence of surveyors, this study proposes a non-contact detection method for measuring sow backfat thickness based on the feature visualization of a residual network. Compared to the VGG16 model and that proposed by YU M et al [31], the R 2 of the model in this study was 0.94 in the test set, which is higher than the R 2 of the other two models, and the MAE was 0.44 mm, which is lower than the MAE of the other two models, indicating that the performance of the model in this study is better than the other two. Secondly, compared to the model before segmentation, the R 2 increased by 3.3% and the MAE decreased by 18.5%, which verifies the feasibility of removing irrelevant features and improving the accuracy of the sow backfat thickness detection model.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In order to solve the problems of time consumption, relative inefficiency, equipment constraints, and the influence of surveyors, this study proposes a non-contact detection method for measuring sow backfat thickness based on the feature visualization of a residual network. Compared to the VGG16 model and that proposed by YU M et al [31], the R 2 of the model in this study was 0.94 in the test set, which is higher than the R 2 of the other two models, and the MAE was 0.44 mm, which is lower than the MAE of the other two models, indicating that the performance of the model in this study is better than the other two. Secondly, compared to the model before segmentation, the R 2 increased by 3.3% and the MAE decreased by 18.5%, which verifies the feasibility of removing irrelevant features and improving the accuracy of the sow backfat thickness detection model.…”
Section: Discussioncontrasting
confidence: 74%
“…VGG16 had strong performance in the classification field [30] but it did not perform very well in this study, with an R 2 of 0.66 and an MAE of 0.66 mm, which were the lowest and the highest, respectively. In this study, the R 2 increased by 42.4% and 23.6%, respectively, and the MAE decreased by 68.3% and 63.3% compared to VGG16 and the model by YU M et al [31], respectively. Therefore, the performance of the model in this study was better than VGG16 and that proposed by YU M et al [31].…”
Section: Comparison Of the Performance Of Different Models In The Tes...mentioning
confidence: 43%
See 1 more Smart Citation
“…Point cloud data or a depth map can be used to acquire more dimensional information, but their accuracy will be affected by the environment with limited scenarios and higher costs [15,16]. Yu et al [17] constructed a CNN-BGR-SVR model to measure the BF of pregnant sows based on 2D images of the sows' backs and used BGR features that took into account the heritability of BF. The study showed that the BF could be non-contact measured using 2D back images.…”
Section: Introductionmentioning
confidence: 99%